HUBUNGAN PERSEPSI SISWA MENGENAI PELAKSANAAN ASAS KERAHASIAAN OLEH GURU BK DENGAN MINAT SISWA MENGIKUTI KONSELING INDIVIDU KELAS VIII SMP NEGERI 2 AMPELGADING PEMALANG - Zulfah Rizqi (JCOSE Jurnal Bimbingan dan Konseling, 2021)
Individual counseling services are one of the services provided by BK teachers to help their students. However, these services have not been fully utilized by students because students' perceptions of BK teachers are not good. These perceptions may influence students' interest in participating in individual counseling services. Looking at this hypothesis, this study will discuss the relationship between student perceptions of the implementation of the principle of confidentiality by counseling teachers with students' interest in participating in individual counseling services. The purpose of this study was to prove the relationship between student perceptions of student interests. The population studied was all students of class VIII SMP Negeri 2 Ampelgading with a sample of 152 people who were randomly selected (random sampling).This research is an ex post facto research. The research data were taken using a psychological scale questionnaire about student perceptions and student interests. All data obtained were then analyzed and tested using the product moment correlation formula. After testing, it was concluded that there was a relationship between student perceptions of student interests. Students' low perceptions are one of the factors for the low interest of students in participating in individual counseling.